Interview with Theo van Leeuwen - Fredrik Lindstrand (Stockholm University Press, 2010)
This issue features an interview with professor Theo van Leeuwen, who is known to most of our readers as one of the main contributors to the field of multimodality and social semiotics. As always, our intention with the interview is to give some further insights regarding interests and influences that form a background to his theoretical work.